How Does Size Affect Mutual Fund Performance? Evidence from Mutual Fund Trades - Busse, Jeffrey (Institutional Knowledge at Singapore Management University, 2013)
This paper uses a unique sample of actual fund trades combined with fund portfolio holdings to investigate why larger mutual funds underperform smaller-size funds. Contrary to the idea that larger funds experience greater transaction costs, we find precisely the opposite: larger funds experience lower percentage transaction costs than smaller funds. Further examination of the characteristics of stocks held by mutual funds shows that smaller funds hold smaller market capitalization stocks and, to a less extent, stocks with greater book-to-market ratios and higher momentum. More importantly, it is these characteristics, especially the market capitalization of stock holdings, that account for diseconomies of scale in the mutual fund industry. Together, our results uncover a new mechanism behind mutual fund diseconomies of scale: it is the avoidance of transaction costs that lead larger funds to hold stocks characterized by lower average returns.